Assessing the role of ageing, feminising and better-educated workforces on TFP growth - Andrea Ariu; Vincent Vandenberghe (National Bank of Belgium, 2014)
This paper uses Belgian firm-level data, covering the 1998-2006 period, to assess the impact on TFP growth of key labour force structural changes: ageing, feminisation and rise of educational attainment. Based on a Hellerstein-Neumark analytical framework, our work shows that an ageing workforce negatively affects TFP growth, whereas its feminisation and its tendency to be better-educated do not have any independent positive or negative impact. Therefore, the TFP slowdown induced by the ageing process is neither gender biased nor counterbalanced by the rising educational attainment of the workforce. These findings are robust to many additional treatments applied to the data, and controlling for the different sources of endogeneity. Quantitatively, ageing workforces account for a -4.5 percentage points loss in terms of cumulative TFP growth over the 1991-2013 period; and the projections suggest that this number could reach -7 percentage points by the mid-2020s. This pattern is not so much dictated by Belgium's demography, but rather its commitment to attain an overall employment rate of 75% by 2020. The latter almost inevitably implies almost doubling the current employment rate of individuals aged 55-64.
Keywords: 330; TFP growth; Ageing; Feminisation; Rising Educational Attainment; Firm-Level Analysis; Produktivitätsentwicklung; Alternde Bevölkerung; Bildungsniveau; Weibliche Arbeitskräfte; Belgien